Confirmatory factor analysis of the Insomnia Severity Index (ISI) and invariance across race: a pooled analysis of MsFLASH data. Issue 8 (August 2019) - Otte, Julie L.; Bakoyannis, Giorgos; Rand, Kevin L.; Ensrud, Kristine E.; Guthrie, Katherine A.; Joffe, Hadine; McCurry, Susan M.; Newton, Kathrine M.; Carpenter, Janet S.
Abstract: Objective: Women's sleep at menopause is widely reported to be problematic. The Insomnia Severity Index (ISI) is a commonly used tool for quantifying sleep problems in clinical and research settings, but psychometric properties in postmenopausal women have not been reported. Our study aim was to examine the factor structure of the ISI in a large and diverse sample of midlife women with hot flashes. Methods: Baseline data were from 899 women enrolled in one of the three clinical trials using similar entry criteria conducted by the Menopause Strategies Finding Lasting Answers to Symptoms and Health research network. We conducted confirmatory factor analyses for the total sample and within strata defined by race/ethnicity (black and white women). Results: The ISI had two factors in the total sample. The two-factor structure was consistent across black and white women, with the exception of one item "difficulty falling asleep." Conclusions: The ISI in midlife women with hot flashes is composed of two factors that capture dimensions of the insomnia severity and daytime impact. The instrument is a psychometrically sound scale appropriate for use in research and clinical practice to capture the severity and daytime impact of insomnia symptoms in diverse samples of midlife women with hot flashes. An abbreviated screening of two items could be considered to determine if further evaluation is needed of sleep complaints.